Hyperglycemia is associated with mortality in pediatric intensive care unit - Castañeda, Alejandra (2023)
Objective: To determine the association between glycemia values and mortality in the Pediatric Intensive Care Unit. The study: Retrospective cohort study in pediatric patients between 1 month and 18 years; hospitalized in the PICU for more than 48 hours. Findings: 184 patients were included. The median age was 33.5 months; mortality was 11.54%. The adjusted analysis showed that maximum glucose in 24 hours and PIM2 scale value could be presented as risk factors for mortality, unlike sex, age, and Glasgow scale value, which were presented as protective factors. Conclusion: In the series evaluated, an association was found between the value of maximum glucose in the first 24 hours and mortality in the PICU. Prospective studies are needed to assess this association.